National Cancer Societies and their public statements on alcohol consumption and cancer risk. (31st May 2018) - Amin, Gopal; Siegel, Michael; Naimi, Timothy
Abstract: Background and aims: Studies have shown that alcohol consumption is a risk factor for oral, pharyngeal, laryngeal, esophageal, liver, colon, rectal and breast cancer. It would therefore be expected that cancer prevention organizations would incorporate these facts into their public stance on the consumption of alcohol. The aims of this study were to: (1) assess how national cancer societies in developed English‐speaking countries [i.e. English‐speaking countries belonging to the Organization for Economic Co‐operation and Development (OECD)] communicate alcohol‐related cancer risk to the public and (2) compare whether these organization's advocacy of increased alcohol taxes is in line with their advocacy of tobacco tax increases to reduce cancer risk. Methods: We searched the websites of the following national cancer organizations for all statements related to the relationship between alcohol consumption and cancer risk: Cancer Council Australia, Canadian Cancer Society, Irish Cancer Society, Cancer Society New Zealand, Cancer Research UK and the American Cancer Society. A categorical system was developed to code the qualitative data for health statements, alcohol consumption recommendations, and tax policy recommendations. Websites were analyzed in March of 2017. Results: All organizations, with the exception of the American Cancer Society and Canadian Cancer Society, state that alcohol is a group 1 carcinogen and that even low‐level alcohol consumption increases risk for some cancers. Additionally, while the American Cancer Society supports increasing tobacco taxes through its cancer action network, it has not advocated for increased alcohol taxes in relation to support for tobacco tax increases. Conclusion: Analysis in 2017 of the websites for national cancer societies in Australia, Canada, Ireland, New Zealand, the United Kingdom and the United States—including Cancer Council Australia, the Canadian Cancer Society, the Irish Cancer Society, Cancer Society New Zealand, Cancer Research UK and the American Cancer Society—shows that only the American Cancer Society and Canadian Cancer Society websites fail to state that alcohol is a group 1 carcinogen and can cause cancer at low doses, and that there is no safe threshold for cancer risk.